Studies on Dielectric, Electrical, Magnetic and Hetero-photocatalytic Properties of Bismuth Layered Aurivillius Oxides - Singh, Shruti (IIT BHU Varanasi, 2022)
Abstract is available in the content
Keywords: Studies on Dielectric, Electrical, Magnetic; Hetero-photocatalytic Properties of Bismuth; Layered Aurivillius Oxides